2017
DOI: 10.5888/pcd14.170052
|View full text |Cite
|
Sign up to set email alerts
|

A Home-Based Type 2 Diabetes Self-Management Intervention in Rural Guatemala

Abstract: IntroductionDiabetes self-management education (DSME) is a fundamental element of type 2 diabetes care. Although 75% of adults with diabetes worldwide live in low-income and middle-income countries (LMICs), limited DSME research has been conducted in LMICs. The objective of this study was to evaluate a home-based DSME intervention in rural Guatemala.MethodsWe conducted a prospective study of a DSME intervention using a quasi-experimental, single-group pretest–posttest design. We enrolled 90 participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Kaselitz et al published a scoping review of policies and interventions for diabetes in LatAm [147], telehealth, mobile clinics, and other non-traditional health care delivery models. In addition, a non-exhaustive list of examples of past or current interventions, policies, and initiatives is provided in Table 4 [184,186,234,[236][237][238][239][240][241][242][243][244][245][246][247][248][249][250][251][252]. Interventions in the list include tele-ophthalmology [249,250,253,254], teambased foot self-care education [236], diabetic retinopathy education and screening at a community pharmacy [255], rapid assessment/diagnostic tools to screen for or detect retinopathy, nephropathy, and risk of developing foot ulcers [201,[256][257][258][259][260][261][262] and are examples of clinical research and/or implementation activities designed to strengthen the prevention and early detection of diabetes-associated complications and improve health outcomes throughout LatAm.…”
Section: Innovative Solutions: Emerging Research and Alternative Modementioning
confidence: 99%
See 2 more Smart Citations
“…Kaselitz et al published a scoping review of policies and interventions for diabetes in LatAm [147], telehealth, mobile clinics, and other non-traditional health care delivery models. In addition, a non-exhaustive list of examples of past or current interventions, policies, and initiatives is provided in Table 4 [184,186,234,[236][237][238][239][240][241][242][243][244][245][246][247][248][249][250][251][252]. Interventions in the list include tele-ophthalmology [249,250,253,254], teambased foot self-care education [236], diabetic retinopathy education and screening at a community pharmacy [255], rapid assessment/diagnostic tools to screen for or detect retinopathy, nephropathy, and risk of developing foot ulcers [201,[256][257][258][259][260][261][262] and are examples of clinical research and/or implementation activities designed to strengthen the prevention and early detection of diabetes-associated complications and improve health outcomes throughout LatAm.…”
Section: Innovative Solutions: Emerging Research and Alternative Modementioning
confidence: 99%
“…Some of the diabetes prevalence studies included in our review focused on or mentioned participants from indigenous groups [35,48,50,74,83] and other underrepresented groups (e.g., Garifuna, Afro-Panamanian, Afro-Peruvian, Afro-Ecuadorian) [55,76,90,91,166]. However, a few studies have evaluated diabetes care, prevalence, and/or prevention of macro-or microvascular complications, diabetes management interventions, other health care needs and access to health care among indigenous populations [241,244,246,[294][295][296][297][298][299][300][301][302], and none on the other groups (that we could identify through our search). Understanding the protective mechanisms (e.g., biochemical, immune, epigenetic) against diabetes experienced by some indigenous populations would be relevant to millions at high risk of developing diabetes.…”
Section: Indigenous and Other Ethnic Underserved Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies of diabetes management in LMICs have shown marked improvements in A1c resulting from reconstitution of medication therapy, particularly when baseline A1c is high. 56,57 However, 2 factors support the importance of the titration algorithm in our program. First, most patients (82%) reported that they were taking medications at the time of enrollment.…”
Section: Medication Titration Attenuation Of Diabetes Control and Mmentioning
confidence: 97%
“…The few studies on T2D performed in LMICs are mainly based on isolated interventions related to training of formal or informal healthcare providers [10,11,12,13], pharmacological follow-up [14] and patient education and counselling [12,[15][16][17][18][19][20]. Despite their seemingly positive short-term effects, managing chronic conditions requires a long-term strategy which involves more than performing a series of disconnected interventions [21].…”
Section: Introductionmentioning
confidence: 99%